Strain-induced molecular orientation in sheared polycarbonate. - Gopez, Adolfo Jesus R. (Philippine Engineering Journal)
Characterization of molecular orientation was done on polycarbonate samples previously deformed in plane simple shear. Birefringence and extinction angle values and x-ray data indicated the presence of molecular orientation. Measurements done on undeformed samples showed no evidence of orientation indicating that the orientation in the deformed sample is strain-induced. A theoretical expression giving birefringence as a function of draw ratio was derived using the pseudo-affine hypothesis. Good agreement was found with the birefringnce data. Comparison with samples deformed in uniaxial tension showed that for the same draw ratio, samples deformed in sample shear had higher birefringence.